Cataract surgery in the extremely small eye: morphology, comorbidities and outcomes in 300 eyes - Hammer, Maximilian; Teich, Lilly; Friedrich, Maximilian; Reitemeyer, Emanuel; Britz, Leoni; Khoramnia, Ramin; Yildirim, Timur Mert; Auffarth, Gerd U. (British journal of ophthalmology, 2025)
Background/aims Data on morphological characteristics and outcomes of extremely short eyes undergoing cataract surgery is sparse. Thus, an in-depth characterisation of eyes implanted with a high-power intraocular lens (IOL) (>30 dioptres) was performed. - Methods In this retrospective cohort study from January 2009 to October 2023, 300 eyes of 191 patients undergoing cataract surgery with extremely short axial length requiring the implantation of a high power IOL>30D were included. Eyes were categorised into the morphologies of nanophthalmos (N), relative anterior microphthalmos (RAM) and high or low/moderate hyperopia (HH and MH). Comorbidities, intraoperative and postoperative complications, preoperative and postoperative refraction and visual outcomes were investigated. - Results Mean preoperative spherical equivalent (SE) was +6±2.85 D. The mean axial length was 20.68±0.92 mm. 19.3%, 45.3%, 22.7% and 12.7% of the studied eyes were categorised as MH, HH, N and RAM, respectively. Amblyopia (14.7%), previous strabismus surgery (7.3%), glaucoma (12.7%) and previous iridotomy (9.4%) were prevalent. Postoperative SE was −0.42±1.56 D. Preoperative Corrected Distance Visual Acuity (CDVA) and postoperative Uncorrected Distance Visual Acuity (UDVA) were not significantly different (0.34±0.39 Logarithm of the Minimum Angle of Resolution (logMAR) vs 0.47±0.38 logMAR, respectively, p=0.47), postoperative CDVA was slightly improved (0.28±0.31 logMAR, p=0.02). The narrow anterior chamber angle was significantly alleviated, posterior capsule rupture rates (3%) were within previously reported ranges. - Conclusions Lens surgery is safe, improves the anterior chamber situation but is rather imprecise in extremely short eyes. Of all subtypes, nanophthalmic eyes showed compromised outcomes. Postoperative CDVA is only slightly improved to preoperative CDVA, while postoperative UDVA closely resembles preoperative CDVA. Surgery thus provides spectacle independence leading to good patient satisfaction.
Online verfügbar: 27. Februar 2025
Gesehen am 11.08.2025